Air Pollution and Green Innovation - Liwen Guo; Zhiming Cheng; Massimiliano Tani; Sarah Cook (Institute of Labor Economics (IZA), 2023)
With air pollution remaining a significant problem in many regions globally, an increasing number of environmentally conscious entrepreneurs have been taking initiatives to combat this issue, accompanied by a growing environmental awareness among the general public. To test the strength of this relationship, we use individual-level information from an enterprise survey in China in 2018 and conducted instrumental variable analyses to study the impact of air pollution on the green innovation behaviours of non-agricultural entrepreneurs. The results indicate that, on average, a one standard deviation increase in PM2.5 concentration is associated with a 4.3 percentage points increase in green innovation (or a 11.9 percentage points increase in green innovation intensity). Entrepreneurs' gambling preferences could potentially mediate the relationship between air pollution and green innovation, while expected firm income and actual firm income may act as suppressors. Specifically, entrepreneurs who launch their businesses following the implementation of environmental policies are more likely to adopt green innovation practices. This study provides insight into why there is a growing trend of environmentally-conscious entrepreneurs in regions with high levels of air pollution.
Keywords: J01; Q53; Q55; 330; green innovation; air pollution; China